Transformation of the organizational culture of civil service employees - EMELYANOVA O. Y.; KRAVETS M.A.; SHERSHEN I.V. (The journal of contemporary issues in business and government, 2020)
The work investigates trends in the activities of state civil servants. The roles that a civil servant should play in modern conditions are determined. Revealed the need to change the skills of officials. The problems of culture of civil servants and directions of its improve- ment are identified.